Strategi Kewirausahaan dan Inovasi Pemasaran dalam Pengembangan UMKM Ayam Kribo - Ratna Sari Dewi; Fenni An’nisa Siregar; Sela Angela; Risdah Armayana; Riska Syahmala (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study discusses the entrepreneurial motivation applied in building and developing the Ayam Kribo culinary business, an MSME located in Patumbak District. This business was pioneered by Mr. Agus, a former daily worker and truck driver, who was inspired by his brother's success in the fried chicken business. With an entrepreneurial spirit, family support, and innovation in taste and service, Ayam Kribo was able to survive various initial challenges and develop into a business with one branch and two employees. This study uses a qualitative case study approach with observation and interview methods. The results of the study show that a combination of personal motivation, product innovation, utilization of social relations, and perseverance are the main factors in business success. The story of Ayam Kribo can be an inspiration for prospective entrepreneurs in starting and managing a business in the culinary sector independently and sustainably.